HPV-ASSOCIATED DISEASES IN THE STRUCTURE OF FEMALE REPRODUCTIVE TRACT TUMORS AND SEXUALLY TRANSMITTED INFECTIONS IN MOSCOW AND RUSSIA - N. I. Briko (Sankt-Peterburg : NIIÈM imeni Pastera, 2018)
The group of female reproductive tract tumors includes cancers of corpus uteri, ovary, cervix, vulva and vagina (the last three are associated with HPV). Among the large group of sexually transmitted infections (STIs) there are only six infections, which subject to registration in the official statistical data in Russia: syphilis, gonorrhea, trichomoniasis, chlamydia, urogenital herpes and anogenital warts (AGWs). Occurrence of AGWs in 95–100% of cases caused by HPV types 6 and 11. Objectives: our aim was to determine the prevalence of HPV-associated diseases (cervical cancer and anogenital warts) in the structure of female reproductive tract tumors and STIs in recent years in Moscow, and to compare it with the prevalence in population of Russia. Methods: we analyzed retrospective data with diagnostic codes related to cancers of corpus uteri, ovary, cervix, vulva and vagina from the official statistic of cancer register using incidence and mortality rates between January 2007 and December 2015 in Russia and Moscow. We also analyzed retrospective data of STIs (incl. syphilis, gonorrhea, trichomoniasis, chlamydia, urogenital herpes and AGWs) incidence rates between January 2003 and December 2015. Results: average rate of cervical cancer incidence among the female reproductive tract tumors accounted for 23.7% in Moscow (29.8% in Russia). Average rate of cervical cancer mortality among the female reproductive tract tumors accounted for 24.1% in Moscow (28.3% in Russia). The rate of AGWs in the STIs structure (for both sexes) in Moscow increased from 11.5% in 2003 to 25.7% in 2015 (the maximum was 31.0% in 2014). The highest rate of AGWs was detected in the age group 15–17 years (up to 59.8% in 2012), followed by 18–29 years (up to 37.3% in 2014). The rate of AGWs was 11.7% among all STIs (in both sexes) in Russia in 2015. Conclusion: HPV-associated diseases (cervical cancer and AGWs) take up a significant place in the structure of female reproductive tract tumors and STIs. And in the structure of the STI for Moscow, AGWs moved from the 5th (in 2003) to the 1st (in 2015) ranked place, surpassing syphilis, gonorrhea, trichomoniasis and chlamydia. The effective prevention of HPV-infection would be able to improve the situation.